Childhood trauma, psychache, and depression among university students: a moderated mediation model - Chen, Shufeng; Fu, Tiantian; Wang, Yiwen; Sun, Guoxiao (Frontiers in Psychiatry, 2024)
Background: Childhood trauma is a potential threat to depression and can have a lifelong impact on the mental health of university students. Our study aimed to construct a moderated mediation model to explore the relationship between childhood trauma, psychache, ambivalence over emotional expression, physical activity, and depression in university students. Methods: A cross-sectional study was conducted in three universities in China, recruiting 476 university students using self-report questionnaires. The moderated mediation model was examined using the SPSS PROCESS model 21. Results: Ambivalence over emotional expression (F=12.843), childhood trauma (F=117.639), and psychache (F=581.594) all had a significant positive effect on depression (p<0.001), explaining 2.9%, 21.7%, and 56.8% of the variance, respectively. On the chain of influence between childhood trauma and depression, the mediating effect of psychache, the moderating effect of ambivalence over emotional expression, and the moderating effect of physical activity are all significant the overall indirect effect value of the three is 0.287, accounting for 61.59% of the total effect. Conclusions: This study investigated the relationship between childhood trauma, ambivalence over emotional expression, psychache, physical activity, and depression in university students. Future interventions should focus on developing good emotional expression among university students, increasing opportunities for physical activity, and reducing psychache to reduce depression.